One Map Policy in The Context of Resolving Overlapping Space Utilization in Bogor, Indonesia - Sri Wahyuningsih; Ratri Istania; Asropi Asropi (Yayasan Riset dan Pengembangan Intelektual, 2023)
Conflicts of overlapping space utilization in Bogor Regency, amounting to 13.2% or 29,204 hectares, were revealed by the Overlap Indication Map. These conflicts stem from duplicate licensing, unsynchronized map standards between Bogor Regency and West Java Province, and inadequate information sharing. To address these issues, the President's strategic direction, based on Presidential Regulation 23/2021 and Government Regulation 43/2021, aims to accelerate the implementation of the One Map Policy at a scale of 1:50,000 with an action plan for 2021-2024. This study uses a qualitative approach and data collection methods including Focus Group Discussions, interviews, and document reviews. The research identifies why the implementation of the One Map Policy in Bogor Regency has been less than optimal and suggests strategies for improvement. Despite the presence of an organizational structure for the policy's implementation, factors hindering its effectiveness include lack of policy objectives, limited resources, insufficient information sharing, lack of leadership support, and lack of understanding of the policy's direction. The study concludes that these issues need to be urgently addressed for optimal implementation of the policy.